المرأة الجديدة في شعر الشاعرات السوريات - الأسد, رداح غصوب (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يمثل النتاج الشعري للشواعر السوريات ظاهرة متميزة ، فالقراءة المعمقة لهذا النتاج تبرز الصوت الشعري للشاعرة السورية التي صوّرت الأوضاع المختلفة للمرأة في صورتها الجديدة ، بعد أن كان لآراء المفكرين والمصلحين دور في النهوض بها ، ودفعها للتحرر من واقعها الذي عانت منه سنيناً طويلة ، ولا سيما قاسم أمين الذي كان حامل لواء تحريرها ، وقد استجابت المرأة لهذه المؤثرات فظهرت أسماء مميزة ، منهن أديبات وشواعر ، وقد امتلك نتاجهن حضوراً قوياً ، ومع بروز عدد كبير من الأسماء الشعرية النسائية ، برز صوت المرأة كصوت مستقل له ذاته ومشاعره وأحاسيسه وسماته التي تعطيه هوية خاصة ، وصوّر الصور الجديدة التي ظهرت عليها المرأة بعد تحررها من القيود المفروضة عليها وبخاصة قيد الرجل . poetic output of Arabic poets represents distinctive phenomenon. Reading this production highlights the poetic voice of the Arabic poet who portrayed different situations of women particularly in her new image. The role of intellectuals and reformers’ opinions in the advancement of women, pushed her to free herself from her reality which she had suffered for many years, especially Qasim Amin , who was the standard bearer of women's liberation, Women responded to these effects which showed distinguished names of writers and poets. Their production possessed significant presence, and with the emergence of large numbers of poetic women's Names, the woman's voice had emerged as an independent voice which had his own emotions , feelings and characteristics that gave it a special identity, portraying new images of women which appeared after her liberation from restrictions imposed upon her, in particular the restriction of man.